Efficacy of prophylactic platelet rich plasma (PRP) following open saphenous vein harvesting in cardiac surgery - Federica Jiritano; Raffaele Serra; Antonio Nenna; Antonio Curcillo; Francesco Villella; Francesco Nappi; Camilla Chello; Massimo Chello; Pasquale Mastroroberto; Giuseppe Filiberto Serraino (Frontiers in Bioscience-Elite, 2022)
Background: Wound infection represents a frequent trouble following open saphenous vein harvesting in cardiac surgery. Platelets’ growth factors are crucial for the healing process. Prophylactic platelet rich plasma (PRP) application on leg wound might reduce the incidence of saphenous vein harvest site infections in patients undergoing coronary artery bypass graft surgery (CABG). Methods: Between January 2009 and December 2020, 987 consecutive patients underwent CABG using saphenous vein as conduit graft and were retrospectively divided into two groups. All patients had standard surgical leg wound closure and wound care, but treatment group received adjunctive topical application of PRP (no-PRP and PRP group, respectively). The primary outcome was wound infection. Results: Saphenous vein harvest site infection rate was similar between PRP (3.5%) and No-PRP (5.2%) group, p = 0.215. The ASEPSIS score was lower for the PRP group (PRP: 3.6 ± 9.1 vs. No-PRP: 5.3 ± 11.2; p = 0.014). Performing a subgroup analysis, the diabetic patients (PRP-DM) group had a lower rate of infection than control group (No-PRP DM) (2.6% vs. 7.7%, p = 0.026). PRP-DM patients had an inferior ASEPSIS score (PRP-DM: 2.7 ± 8.3 vs. No PRP-DM: 7.5 ± 13.2, p < 0.001). Conclusions: Topical application of autologous PRP on saphenoug vein harvest site might reduce the rate of surgical site infection, with particular benefit among diabetic patients.